Research Trends of Biodegradation of Cooking Oil in Antarctica from 2001 to 2021: A Bibliometric Analysis Based on the Scopus Database - Zahri, Khadijah Nabilah Mohd; Zulkharnain, Azham; Sabri, Suriana; Gomez Fuentes, Claudio German; Ahmad, Siti Aqlima (My University, 2021)
In the present age, environmental pollution is multiplying due to various anthropogenic activities. Pollution from waste cooking oil is one of the main issues facing the current human population. Scientists and researchers are seriously concerned about the oils released from various activities, including the blockage of the urban drainage system and odor issues. In addition, cooking oil is known to be harmful and may have a carcinogenic effect. It was found that current research studies and publications are growing on these topics due to environmental problems. A bibliometric analysis of studies published from 2001 to 2021 on cooking oil degradation was carried out using the Scopus database. Primarily, this analysis identified the reliability of the topic for the present-day and explored the past and present progresses of publications on various aspects, including the contributing countries, journals and keywords co-occurrence. The links and interactions between the selected subjects (journals and keywords) were further visualised using the VOSviewer software. The analysis showed that the productivity of the publications is still developing, with the most contributing country being the United States, followed by China and India with 635, 359 and 320 publications, respectively. From a total of 1915 publications, 85 publications were published in the Journal of Agricultural and Food Chemistry. Meanwhile, the second and third of the most influential journals were Bioresource Technology and Industrial Crops and Products with 76 and 70 total publications, respectively. Most importantly, the co-occurrence of the author's keywords revealed "biodegradation", "bioremediation", "vegetable oil" and "Antarctic" as the popular topics in this study area, especially from 2011 to 2015. In conclusion, this bibliometric analysis on the degradation of cooking oil may serve as guide for future avenues of research in this area of research.
Keywords: biodegradation; bioremediation; cooking oil; antarctic